Social and Governance Dimensions of Climate Change: Implications for Policy - Foa, Roberto (Washington, DC: World Bank, 2012)
This paper addresses two vital concerns in the debate on adaptation to climate change. First, how can countries prepare to manage the impact of climate-change induced natural disasters? Second, how can countries ensure that they have the governmental institutions required to manage the phenomenal challenge of adaptation to climate change? A range of economic and institutional measures are tested for their potential effects on natural disaster resilience and the quality of environmental governance. The findings suggest an important role is played by social and political institutions in determining the ability of countries to adapt to climate change and respond to natural disasters, in particular in the degree to which countries have succeeded in gender empowerment and the development of a robust civil society and nonprofit sector. As the climate change challenge moves from that of 'proving the facts' to that of 'implementing change' the authors suggest that international policymakers, donors, and activists must increasingly focus on building domestic policy environments that are conducive to the delivery of more effective environmental legislation, for example through implementation of gender quotas and provision of support to civil society groups.